Report of N.D.C. Committee on Micro-Level Planning and Involvement of People at Grass Root Level - Planning Commission (Planning Commission Government of India, 1993)
The NDC Committee Report on Micro-Level Planning and People Involvement emphasizes the critical role of grassroots participation in achieving equitable rural development in India. Chaired by Shri Chimanbhai J. Patel, the report advocates using the block as the planning unit, integrating local plans, and decentralizing authority and funds to strengthen the Panchayat system. Key recommendations include allocating at least 30% of state plan outlays for micro-level planning, capacity building for local officials, robust data management, and active engagement of NGOs, youth, and village stakeholders. By fostering participatory democracy, the report envisions development strategies that are locally responsive, inclusive, and sustainable.
Government of India Planning Commission April, 1593
Keywords: Grassroots Development; Panchayat System; Decentralization; Resource Allocation; Capacity Building; Inclusive Governance; Village Development Committees; Participatory Democracy; Local Knowledge; Rural Livelihoods